(untitled) (Global Journal of Human-Social Science, 2019)
The study examined the impact of agricultural output on economic growth in Nigeria from 1985 to 2015. The econometrics methods of Ordinary Least Squares, Cointegration, and Granger causality test were employed as the main analytical techniques. The Co-integration results revealed that there exists a long-run relationship between the variables. The short run regression result revealed that Commercial Banks’ credit to the agricultural sector and the interest rate has a significant relationship with economic growth in Nigeria during the period of study. While, agricultural output has no significant relationship with economic growth in Nigeria during the studied period. The study therefore concluded that suitable or effective agricultural output enhancement policy should be put in place by the government. There should be appropriate interest rate policies that would bring about the stability of the economy and economic growth. Without agricultural produce to keep the people alive as well as lubricating our machines with agricultural oil, there can be no growth. Everything is sustained by agriculture and without it, there shall be no true living. Also, conscious efforts should be made by the monetary authorities with the emphasis on funding agriculture in order to increase economic growth in Nigeria. This can be achieved if the government avoids mismanagement, and diversifies the economy.